Reconsidering the role of ulema and scribal actors in the ottoman transition from manuscript to the printed medium - BAŞARAN, AYŞE (My University, 2023)
Scholarship on the Ottoman printing enterprise has long neglected the part played by the traditional actors of the written word, including the ulema and calligraphers, in the rise of the press. Though traditionally viewed as opponents of the new print technology, these actors continued to fulfill vital roles in everything from editorial work to the techno- material aspects of printing, generating new opportunities for themselves in a rapidly changing cultural environment. This paper focuses on their role in the Imperial Press to reveal how the know-how of these actors was critical for the transition to the new Ottoman cultural medium of print. It further suggests that as these actors adapted andcarried their skills to that medium, they themselves were influenced by the new technology of the press, and the novel ways of relating to the written word that came with it, in a profound way, with significant implications for the nature of scholarship and the shape of the scholarly career track during the period.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Osmanlı Müesseseleri ve Medeniyeti Tarihi; Social Sciences and Humanities; History; History of The Ottoman Instutionsand Civilization; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; TARİH; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; HISTORY; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities